Catalysts for single-wall carbon nanotube synthesis—From surface growth to bulk preparation. (10th November 2017) - Zhao, Xiulan; Zhang, Shuchen; Zhu, Zhenxing; Zhang, Jin; Wei, Fei; Li, Yan
Abstract: Abstract : Catalysts play essential roles in the chemical vapor deposition of single-wall carbon nanotubes (SWCNTs). In this article, we summarize studies on catalysts for the structure-controlled growth and mass production of SWCNTs, discussing the main progress and the remaining challenges.